1980
DOI: 10.1111/j.1528-1157.1980.tb04295.x
|View full text |Cite
|
Sign up to set email alerts
|

Immunological Aspects of Epilepsy

Abstract: Epileptogenic activity can be provoked in animals by topical application on the cerebral cortex of antiserum to brain tissue. Several patients with epilepsy have an immunoglobulin A (IgA) deficiency, which may be caused by antiepileptic drugs (drug-induced) or may apparently be associated with the epileptic condition (drug-independent). Deficiency of secretory IgA may pre-dispose the patients for recurrent upper respiratory infections. Some antiepileptic drugs may also reduce the number of circulating T-lympho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
43
1
1

Year Published

1987
1987
2016
2016

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 73 publications
(47 citation statements)
references
References 43 publications
2
43
1
1
Order By: Relevance
“…more severe attacks are accompanied by worsening of neuroimmune dysregulation (Prokhorova; 2011). Thus, we observed a significant elevation of antibodies to protein S100 in both subgroups, greater in idiopathic epilepsy, compared to the control (54.3±10.3; membrane, thereby, increasing the spiking activity of cells on EEG (Aarli, 1993(Aarli, , 2000. This may indicate a violation of glial relationships and their role in the pathogenesis of epilepsy, especially in idiopathic one.…”
Section: Resultsmentioning
confidence: 54%
See 2 more Smart Citations
“…more severe attacks are accompanied by worsening of neuroimmune dysregulation (Prokhorova; 2011). Thus, we observed a significant elevation of antibodies to protein S100 in both subgroups, greater in idiopathic epilepsy, compared to the control (54.3±10.3; membrane, thereby, increasing the spiking activity of cells on EEG (Aarli, 1993(Aarli, , 2000. This may indicate a violation of glial relationships and their role in the pathogenesis of epilepsy, especially in idiopathic one.…”
Section: Resultsmentioning
confidence: 54%
“…The study of immunological aspects is associated not only with the question of immunosuppressive effect of many anticonvulsants, but also includes the study of immunopathogenesis of epilepsy with questions predicting disease outcome (Poletaev et al, 2004). Aarli (1993Aarli ( , 2000, Poletaev (1997Poletaev ( , 2004, Gusev et al (2006) and Lusnikova (2008) proved the role of the number of autoantibodies to the proteins S100, GFAP, MR65, NGF, neurotransmitters glutamate, GABA, dopamine, and serotonin. However, in the studied literature, we have found no study devoted to the role of antibodies to proteins NF-200, GFAP, DNA and myelin basic protein (MBP) in idiopathic and symptomatic epilepsies.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, many immunological abnormalities have been labeled in patients with epilepsy. Studies have shown that epilepsy develops in several immune-mediated conditions such as SLE, myasthenia gravis and IgA deficiency [11,14] Several immunoglobulin abnormalities which are described in patients with epilepsy, in part associated with anti-convulsant therapy, as well as a high prevalence of anticardiolipin and antinuclear antibodies have been seen in patients with epilepsy [11,15]. Therefore, epilepsy in a number of patients may be due to an immune process, and the association between CD and epilepsy may be the susceptibility of immune-mediated conditions to occur together.…”
Section: Discussionmentioning
confidence: 99%
“…The immunodeficiency associated with HIV infection is obvious; immunodeficiencies and immune dysregulatory effects associated with drugs such as the anticonvulsants phenytoin and carbamazepine [47] may be more subtle but still contribute to an altered response to drugderived neoantigens or self-antigens.…”
Section: The Role Of Infection and 'Molecular Mimicry'mentioning
confidence: 99%